Programa de inteligencia emocional para mejorar el clima institucional de la Institución Educativa “Carlos Manuel Cox Rosse”, La Esperanza, 2018 - Ciudad Gamboa, Maria Beatriz (2019)
The present research work has as an objective to demonstrate that the emotional_x000D_ intelligence improves significantly the institution's institutional climate “Carlos Manuel_x000D_ Cox Roose” of theDistrict La Esperanza, in 2018. The purpose to develop the dependent_x000D_ and independent variable is to improve the institutional behavior skills, organizational_x000D_ skills, and institutional dynamics, and applying emotional intelligence at work and life._x000D_ The test was made to only one group of twenty- three people between principals and_x000D_ teachers, with a pre-experimental design of pre-test and post-test. An institutional climate_x000D_ survey was used as an instrument ofmeasure._x000D_ The final results demonstrate that the emotional intelligence program improves the I.E_x000D_ “Carlos Manuel Cox” institutional climate since in the institutional behavior scale_x000D_ obtained a value of 35.56 for the pre-test and a value of 47.16 for the post-test, where it_x000D_ can be noticed that there was an average increment in relation with the institutional_x000D_ climate; likewise the organizational skills scale obtained a value of 23.08 for the pre-test_x000D_ and 27.44 forthe post-test, in relation with the institutional climate; on the other hand, in the_x000D_ dynamic institutional scale was observed with a value of 37.96 for the pre-test and a value_x000D_ of43.44 for thepost-test._x000D_ Therefore, the results evidenced that the emotional intelligence program improved_x000D_ significantly the institutional climate of theeducative institution at the primary level.